FTA Highlight No.15 – Advancing Gender Equality and Social Inclusion - Elias, M.; Paez Valencia, Ana Maria; Ihalainen, Markus; Monterroso, I. (CGIAR Research Program on Forests, Trees and Agroforestry, 2021)
This publication reflects on FTA’s decade-long journey to advance gender equality in forest, tree and agroforestry landscapes to glean lessons and continue building on the achievements of the Program. The discussion follows the two interconnected and mutually-reinforcing strands detailed in the FTA Gender Strategy (2013) and Revised Research Agenda and Action Plan (2020) to achieve this goal. The first strand focuses on the research itself and the partnerships and processes that allow it to translate into outcomes and impacts of various types. The second strand, which this publication tackles at the beginning, focuses on efforts to strengthen gender integration within FTA: generating the necessary capacities, mindsets, and enabling environment to integrate gender across the FTA research portfolio, processes and structures, and to generate quality gender-focused research. The publication moves from local-level changes to high-level discourses and agendas to examine the strategies that enabled change across these scales, critically reflecting on the challenges encountered along the way. Finally, priorities are considered and an agenda for future gender research is proposed, one that can contribute to the creation of equitable, inclusive and sustainable forest, tree and agroforestry landscapes.